Mental Disorders Among Health Care Workers at the Early Phase of COVID-19 Pandemic in Kenya; Findings of an Online Descriptive Survey - Kwobah, Edith Kamaru; Mwangi, Ann; Patel, Kirtika; Mwogi, Thomas; Kiptoo, Robert; Atwoli, Lukoye (Frontiers in Psychiatry, 2021)
Abstract Background: There is evidence that frontline healthcare workers responding to the Corona Virus Pandemic (Covid-19) are at risk of mental illness. Data is not available for healthcare workers in Kenya that can inform mental health and psychosocial support. The purpose of this study therefore was to establish the prevalence and associated factors of anxiety, depression, posttraumatic stress disorder and poor quality of sleep among Kenyan health care workers at the beginning of COVID-19 pandemic. Methods: We conducted an online survey among 1259 health care workers Kenya. A researcher developed social demographic questionnaire and several standardized tools were used for data collection. The tools were programmed into Redcap, (Research Electronic Data Capture) and data analysis was performed using R Core Team. In all analysis a p-value less than 0.05 was considered significant. Results: 66% of the participants were significantly worried Covid-19, 32.1% had depression, 36% had generalized anxiety, 24.2% had sleeping difficulties 64.7% had some probable PTSD. Depression was higher among females compared to men (36.5% vs 26.9), workers less than 35 years old (38.1% vs 26.4%), and those who were not married (40.6% vs 27.6%). Generalized anxiety was higher among workers aged less than 35 years (43.5% vs 29.3%), females (41.7% vs 29.2%), those who mere not married compared to the married (45.2% vs 31.2%) and those with less than 10 years working experience (41.6 to 20.5%) Insomnia was commoner among younger health care workers compared to those above 35 years of age (30.3% vs 18.6%). Conclusion: Kenyan healthcare workers in the early phase of Covid-19 pandemic suffer from a high burden of various common mental disorders with young, female professionals who are not married bearing the bigger burden. This is a guide for mental health and psychosocial support for healthcare workers in order to optimize productivity.